Conceptual model of the recursive entity modelling method after revision - Rifai Amal; Tzemmout Mohamed Amine; Sadiq Abdelalime (Institute of Advanced Engineering and Science, 2021)
In this work, we present the rectifications that we brought on recursive entity modeling method into lasts articles. Then, we establish the recursive entity modeling method global conceptual diagram in order to conceive a space name and database for this method in future works. Therefore, in the first section, we present an overview of the recursive entity modeling method conceptual model; then, in the second section, we present recursive entity modeling method revisited elements (relationships, component, roles, conception, path, node, connection); and in the third section, we conceive a general conceptual diagram describing the components of the recursive entity modeling method.